Karakteristik Bioplastik Berbasis Pati Talas Belitung dengan Penguat Selulosa Kulit Nanas dan Pemlastis Sorbitol - Yiyin Nanisha; Sukmiyati Agustin (AGRITEKNO: Jurnal Teknologi Pertanian, 2025)
Bioplastics are plastics made from natural polymers such as starch, cellulose, and sorbitol that are biodegradable. Belitung taro, which contains amylose and amylopectin, plays a crucial role in gel formation, providing flexibility, thermal stability, and biodegradability to bioplastics. Cellulose is a strong, hard, biodegradable, and renewable material, making it a potential additive for bioplastics. Sorbitol is used as an additive to increase the flexibility of bioplastics. This study aims to investigate the effect of incorporating pineapple peel cellulose and sorbitol into Belitung taro starch-based bioplastics. The process involves extracting cellulose from pineapple peel waste, producing bioplastics using the solvent casting method, and testing the mechanical and physical properties of these bioplastics. This research was conducted in a Completely Randomized Design with two factors: the addition of cellulose (3, 4, and 5 g) and sorbitol (3, 4, and 5 g). The data were analyzed using ANOVA and Tukey's test at a 5% significance level. The results indicate that the addition of cellulose and sorbitol has a significant impact on thickness, but no significant effect on water vapor permeability, opacity, solubility, or biodegradation. The color of the bioplastic tends to be blue-gray. Tensile strength meets the BSN 2014 and JIS 2019 standards, with values ranging from 4.322 to 10.110 N/mm², while elongation meets the BSN 2014 standard (39%). The low water vapor permeability (0.0027–0.0094 g/m²/day) and high opacity (5.85–8.91 abs/mm) of the bioplastic produced indicate its potential as UV-resistant food packaging. The bioplastic solubility (0.12–0.25%) meets standards, and the degrades after 14 days of burial according to BSN 2014. Although thickness and permeability do not yet meet standards, this bioplastic is economical with low production costs.